PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP NON PERFORMING LOAN (NPL) PADA BANK KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arse, Nikyta Agnadya; Rahman, Fauziah; Dewi, Sucitra (Gapenas Publisher, 2024)
This study aims to determine the effect of capital adequacy ratio (CAR), loan to deposit ratio (LDR), and operating costs operating income (BOPO) on non performing loan (NPL) in conventional banks listed on the Indonesia Stock Exchange (IDX) in 2019 -2021. The population of this study was 43 conventional banks registered on the IDX. Data was collected using a purposive sampling technique, so that 10 conventional bank samples were obtained for 3 years of observation (2019-2021). The research technique used in this study is quantitative research techniques. The data analysis techniques used are descriptive analysis, multiple linear analysis, classical assumption testing, and hypothesis testing using the SPSS application. The results of this study are that partially CAR and BOPO have a positive and significant effect on NPL, LDR has a negative and significant effect on NPL. Simultaneously, CAR, LDR and BOPO together have a significant effect on NPL in conventional banks listed on the IDX in 2019-2021